Um estudo sobre os indicadores de referência de bem-estar no município de São Paulo (IRBEM) - Dias, Vivian Valério (2010)
It has become aware, through the nineties, that the growth of economy is affecting its several sectors and reaching dimensions never considered before. Studies related to the environment and society, search for solutions that bring balance between growth and the preservation of natural resources, aiming and that such actions are appropriate in a social level. Through this thought, the concept of sustainable development was created and it has brought attention and growing concerns to the well-being of the population. For this reasoning and this new conscience to have influence in the decision making the access to relevant data it is considered indispensable. In this matter, indicators (tools that help analyze, quantify and simplify the reading of technical information directed to several organizations, institutions and groups of people) are used and developed. In this path there are still many difficulties, indicators generally used for decision making in political aspects, for example, economic and social indicators do not consider the impacts of other sectors. An economic indicator does not consider the social or environment impacts, as well as social indicators do not consider environment or economic effects, in the same way that, environment indicators do not disclose social or economic impacts. The sustainability brought the concept of synergy among the three sectors, the economy, the environment and the society and it has provided the creation of comparative indicators or sustainability indicators. The purpose of this study is to display the current situation of the sustainability and well-being indicators, aiming to explain its constitution, relevance and influence in political decisions. Its main focus will be to follow the development and construction of IRBEM (Reference Indicators of Well-Being in the City), a project directed by MNSP (Our São Paulo Movement)